2021
DOI: 10.1038/s41396-021-00994-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of viruses inhabiting the deepest ocean on Earth

Abstract: As the most abundant biological entities on the planet, viruses significantly influence the overall functioning of marine ecosystems. The abundance, distribution, and biodiversity of viral communities in the upper ocean have been relatively well studied, but our understanding of viruses in the hadal biosphere remains poor. Here, we established the oceanic trench viral genome dataset (OTVGD) by analysing 19 microbial metagenomes derived from seawater and sediment samples of the Mariana, Yap, and Kermadec Trench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 112 publications
9
87
0
Order By: Relevance
“…With a water depth >6000 ​m, the hadal zone represents one of the least-studied environments on the planet, and it is an indispensable part of the ocean ( Jamieson et al., 2010 ). A recent study has shown that hadal viruses (mainly bacteriophages) harbor unprecedented genomic novelty and are ecologically important ( Jian et al., 2021 ). Nevertheless, only a single phage, PstS-1, was previously isolated from the abyssal environment (the seawater of the Japan Trench at a depth of 7000 m) ( Yoshida et al., 2015 ).…”
mentioning
confidence: 99%
“…With a water depth >6000 ​m, the hadal zone represents one of the least-studied environments on the planet, and it is an indispensable part of the ocean ( Jamieson et al., 2010 ). A recent study has shown that hadal viruses (mainly bacteriophages) harbor unprecedented genomic novelty and are ecologically important ( Jian et al., 2021 ). Nevertheless, only a single phage, PstS-1, was previously isolated from the abyssal environment (the seawater of the Japan Trench at a depth of 7000 m) ( Yoshida et al., 2015 ).…”
mentioning
confidence: 99%
“…In fact, the discovery of Phycodnaviridae viruses in the sediments of the Mariana Trench is not unusual. The sequences of eukaryotic algal viruses have also been detected in the Baltic Sea subseafloor sediments ( 47 ), the sediments of Loki’s Castle hydrothermal vent (∼3,200 m below sea level) in the mid-Atlantic Ocean ( 29 ), and the abyssopelagic Yap Trench sediments ( 48 ). The presence of phytoplankton viruses might be explained if viruses cosink with eukaryotic phytoplankton from the upper water column via the sinking mechanism of the biological pump ( 47 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, BLAST analysis of viral scaffolds was also performed against the Integrated Microbial Genome/Virus (IMG/VR) system v.3.0 database ( 88 ) (BLASTn E value of ≤10 −5 , similarity of ≥90%, and covered length of ≥75%) to assign the taxonomies for viral scaffolds based on sequence similarity ( 49 , 83 ). Additionally, a majority-rules approach was performed for the taxonomic assignments as previously described ( 48 , 88 ). Briefly, predicted proteins from viral scaffolds were compared to NCBI viral RefSeq proteins (release 203) using DIAMOND v2.0.4 ( 89 ) (BLASTp; -subject-cover 50; –more-sensitive; -query-cover 50; -evalue 1e-5), and a viral scaffold was assigned to a taxonomy if ≥50% of the proteins were assigned to that taxonomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has broadened our understanding of the viral world, especially of viruses that infect microbes. It is now universally recognized that viruses are the most abundant biological entities on the Earth ( Jian et al, 2021 ) and have contributed substantially to the evolution of life. In this general context, the scientific community began to take an interest in amoeba viruses in the early 2000s.…”
Section: Introduction: the Rise Of Amoebal Virologymentioning
confidence: 99%